Pengaruh Komunikasi Organisasi terhadap Kinerja Guru: Peran Mediasi Motivasi dan Kepuasan Kerja - YUDO HANDOKO; Sri Rahmah Ramadhoni; Fitriana, Fitriana (PT. Intelek Cendikiawan Nusantara, 2024)
This study aims to investigate the influence of organizational communication on teacher performance, considering the mediating roles of work motivation and job satisfaction. The research employed a quantitative method with a survey approach on a sample of 50 teachers at SMA Negeri 4 Tanjung Jabung Timur. Valid and reliable questionnaire instruments were used to collect data, which was then analyzed using Structural Equation Modeling (SEM) through statistical software such as AMOS or SmartPLS. The results show that organizational communication has a significant influence not only directly on teacher performance but also indirectly through increased motivation and job satisfaction. Effective communication enhances teachers' understanding of school goals and policies, which strengthens their commitment and involvement in the educational process. These findings underscore the importance of developing effective communication strategies in the school environment to support teacher performance and professional development. From this research, it is recommended that schools focus on developing participatory two-way communication, where teachers are actively involved in decision-making. This is expected to create a conducive work environment, increase motivation, and job satisfaction, which will ultimately improve teacher performance. This study makes a significant contribution to educational management literature by identifying and analyzing factors that affect teacher performance in the educational environment.